2005
DOI: 10.1111/j.1471-8286.2005.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic microsatellite loci isolated from the great scallop, Pecten maximus (Bivalvia: Pectinidae)

Abstract: We isolated and characterized nine polymorphic microsatellite loci from the great scallop (Pecten maximus) as part of an attempt to better understand the population–genetic structure of this species. Levels of genetic diversity were assessed in 32 scallops collected from the coastal waters of Port Erin Bay, Isle of Man. The number of alleles ranged from two to 29 and observed and expected heterozygosities varied between 0.031 to 0.906 and 0.062 to 0.973, respectively. Two loci showed significant (P < 0.05) het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The new microsatellites display the same range of variability as those described previously in P. maximus by Watts et al (2005), which were also isolated from genomic DNA. In contrast, the present markers are more polymorphic than those identified by Charrier et al (2012) that were derived from expressed sequence tags (Na varying from 2 to 11 alleles, and H o from 0.05 to 0.84).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The new microsatellites display the same range of variability as those described previously in P. maximus by Watts et al (2005), which were also isolated from genomic DNA. In contrast, the present markers are more polymorphic than those identified by Charrier et al (2012) that were derived from expressed sequence tags (Na varying from 2 to 11 alleles, and H o from 0.05 to 0.84).…”
Section: Discussionmentioning
confidence: 59%
“…Null allele frequency estimates were computed using CERVUS 3.0. The eight best quality loci were selected for the multiplexing process, in addition to three loci from the literature: LIST-15_005 and LIST-15_012 (Watts et al 2005) and PmGC05 (Charrier et al 2012). …”
Section: Statistical Analysis For Microsatellite Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of polymorphic microsatellite loci obtained with respect to the total sequences examined in A. opercularis (6.0%) is higher than that yielded by enriched libraries constructed in the scallop Mizuhopecten yessoensis (4.6%, An et al 2005), the oyster Crassostrea virginica (2.4%, Reece et al 2004) or the pearl oyster Pinctada maxima (0.2%, Evans et al 2006), and lower than that obtained in other scallops, Chlamys farreri (12.5%, Zhan et al 2007), Pecten maximus (15.8%, Watts et al 2005) and C. nobilis (27.5%, Ma and Yu 2009) or the oyster C. gigas (19.6%, Li et al 2003). The efficiency of the isolation of microsatellites as usable markers might be affected by both biological and technical factors.…”
Section: Discussionmentioning
confidence: 62%
“…In other scallop species, such as Mizuhopecten yessoensis and Aequipecten opercularis (Arias et al 2010), minisatellites have also been found in clones with microsatellites, but in these cases they are near or surrounding the microsatellite. The number of polymorphic microsatellite loci obtained with respect to the total sequences examined in Mimachlamys varia (5.62%) was within the range observed for other species where enriched libraries were examined; values obtained in other species were 4.55% in Mizuhopecten yessoensis ), 6.02% in A. opercularis (Arias et al 2010), and 15.79% in Pecten maximus (Watts et al 2005). The abundance of microsatellites and their location in the genomes may explain the differences observed among species in the success of establishing reliable microsatellite markers (Meglécz 2007).…”
Section: Discussionmentioning
confidence: 89%